2010
DOI: 10.3354/ame01346
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial production and respiration in subtropical Hong Kong waters: influence of the Pearl River discharge and sewage effluent

Abstract: Hong Kong waters are influenced by the Pearl River discharge in the west, coastal/ oceanic waters in the east, and year-round domestic sewage effluent in the Victoria Harbour area. Seven cruises were conducted at 12 stations across the Hong Kong water in the dry and wet seasons to examine how the Pearl River outflow and sewage effluent discharge influenced the distributions of dissolved oxygen (DO), dissolved inorganic carbon (DIC), bacterial production (BP) and bacterial respiration (BR). Surface DO saturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 55 publications
(65 reference statements)
3
25
0
1
Order By: Relevance
“…Harrison et al (2008) concluded that there is no massive hypoxia in the lower Pearl River estuary due to a short residence time of the seawater. Hence, the eutrophication impact in Hong Kong waters was not as severe as expected for such a eutrophic area in the wet season (Ho et al, 2008;Yuan et al, 2010a), as DO remained >150 µM with solubility ranging from 210 to 240 µM (Fig. 4a).…”
Section: Influence Of the Pearl River Discharge And Sewage Effluentmentioning
confidence: 93%
See 3 more Smart Citations
“…Harrison et al (2008) concluded that there is no massive hypoxia in the lower Pearl River estuary due to a short residence time of the seawater. Hence, the eutrophication impact in Hong Kong waters was not as severe as expected for such a eutrophic area in the wet season (Ho et al, 2008;Yuan et al, 2010a), as DO remained >150 µM with solubility ranging from 210 to 240 µM (Fig. 4a).…”
Section: Influence Of the Pearl River Discharge And Sewage Effluentmentioning
confidence: 93%
“…Data on salinity, temperature, primary production, DO, DIC and pCO 2 at stations 1 to 8 were presented in Ho et al (2008 and and Yuan et al (2010a). In this study, these data along with wind, respiration and gaseous air-sea fluxes were grouped into three main regions (Pearl River estuary, Victoria Harbor and eastern waters) and two seasonal patterns.…”
Section: Statistical Analyses and Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high and continuous input of allochthonous nutrients and organic material from the surrounding lands and the domestic sewage leads to high phytoplankton and bacterial growth (BARRERA-ALBA et al, 2008;GAULKE et al, 2010;VALENTIN, 2008b;MORTAZAVI et al;SCHUMANN et al, 2003;YUAN et al, 2010). However, most of estuarine BGE in situ estimates were performed in temperate zones, with few exceptions on the tropics (GUENTHER et al, 2008a;LEE et al, 2009;RAM et al, 2003;RAM et al, 2007).…”
Section: Introductionmentioning
confidence: 99%